(untitled) - John Eastwood (Oxford, NY, 1997)
The book is a systematic account of grammatical forms and the way they are used in standard British English today. It is equally suitable for quick reference to details and for more leisured study of broad grammar topics.
Keywords: english grammar,english language; study and teaching,grammar